2016
DOI: 10.3906/sag-1507-187
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of bone marrow-derived mesenchymal stem cellsand conditioned medium in mechanically injured neuroblastoma cells

Abstract: IntroductionStem cells exhibit self-renewal characteristics that distinguish them from other cell types. Major subtypes include totipotent cells, which can divide to produce all cells in an organism, pluripotent cells, which are able to differentiate into any of the three germ layers (endoderm, ectoderm, or mesoderm), and multipotent cells, which can produce multiple cell types within a given lineage (1). Mesenchymal stem cells (MSCs) constitute a class of multipotent cells capable of differentiating into many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(36 reference statements)
0
11
0
1
Order By: Relevance
“…The neuroprotective effects of MSCs -CM could be explained by its capacity to reduce oxidative stress and inhibit the release of both 3-Nitrotyrosine (3-NT) and Nitric Oxide Synthase (iNOS). Moreover, nerve growth factor and brain-derived neurotrophic factor, which decrease reactive astrogliosis were detected in significant amounts in MSCs -CM derived from bone marrow of rats [16,42].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The neuroprotective effects of MSCs -CM could be explained by its capacity to reduce oxidative stress and inhibit the release of both 3-Nitrotyrosine (3-NT) and Nitric Oxide Synthase (iNOS). Moreover, nerve growth factor and brain-derived neurotrophic factor, which decrease reactive astrogliosis were detected in significant amounts in MSCs -CM derived from bone marrow of rats [16,42].…”
Section: Discussionmentioning
confidence: 97%
“…In addition MSCs -CM can modulate the inflammatory environment, enhance vascularization of the regenerating site, increase thickness of the myelin sheaths, accelerate fibre regeneration and reduce of fibrotic scaring and improve fibre organization. Some former workers [42] reported that MSCs -CM have several benefits over MSCs as they can be manufactured, freeze-dried, packaged, and transported more easily than stem cells.Moreover, CM does not contain living cells, so there is no need to do donor recipient matching to avoid rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic index was determined as the ratio of positive-labeled cells to all cells in the chosen fields. The percentage of apoptotic cells was calculated by a blinded observer as follows: 0, no apoptosis; 1, 1%-10% apoptosis; 2, 11%-25% apoptosis; 3, 26%-50% apoptosis; 4, 51%-75% apoptosis; and 5, >75% apoptosis (15,16).…”
Section: █ Discussionmentioning
confidence: 99%
“…Cells were than rinsed in distilled water and mounted in the mounting medium. TUNEL-positive staining was evaluated by the blinded observer under an Olympus BX40 light microscope [12] . Percentage and intensity of the immunostaining were scored with H-scoring and showed as the ratio of positively labelled cells to all cells in the chosen fields.…”
Section: Tunel Assaymentioning
confidence: 99%
“…The percentage of apoptotic cells were also checked out by a blinded observer as 0: no apoptosis, 1: 1%-10% apoptosis, 2:11%-25% apoptosis, 3: 26%-50% apoptosis, 4: 51%-75% apoptosis, and 5: more. than 75% apoptosis [12] . The apoptotic index was counted up as the percentage.of apoptotic cells relative to the total cell number.…”
Section: Apoptotic Indexmentioning
confidence: 99%